Evaluation of the Implementation of Restorative Justice Based on Police Regulation Number 8 of 2021 in Handling Crimes of Persecution - Syahputra Ginting, Erwin; Zarzani, T. Riza; Aspan, Henry (International Conference Epicentrum of Economic Global Framework, 2026)
The high number of criminal acts of persecution in Indonesia is a serious burden on the national criminal justice system which tends to be retributive. Police Regulation Number 8 of 2021 is present as a normative breakthrough that provides a legal basis for investigators in implementing restorative justice at the investigation level. This study aims to evaluate the effectiveness of the implementation of restorative justice based on the Perpol in handling persecution cases as well as formulate an optimization model. The method used is empirical juridical with a statute approach, conceptual approach, and case approach, through literature studies, in-depth interviews with investigators and the Criminal Investigation Office, and analysis of case documents. The results of the study show that the implementation of restorative justice at the investigation level has been procedurally successful, but it has not been optimal substantively due to limited investigator capacity, inconsistency in the implementation of requirements, weak supervision, and inadequate victim protection. Optimization requires strengthening technical regulations, standardizing national SOPs, improving investigator competence, stronger internal supervision, and affirming victim protection mechanisms so that restorative justice is able to realize substantive justice, legal certainty, and balanced benefits.